Harnessing Green Nitrogen-Doped Zinc Oxide for Efficient Methylene Blue Dye Photocatalytic Degradation in Wastewater Treatment - Ummu Humairah Hashim; Shahzulaikha Aiman Mohmed; Syahida Suhaimi; Maisurah Mukhtar; Nur Athirah Mohd Taib; Imam Tazi (Malaysian Journal of Science Health & Technology, 2025)
Photocatalysis remains a promising solution for water treatment due to its efficiency, sustainability, and ability to degrade a wide range of contaminants. This study explores the green synthesis of zinc oxide (ZnO/GS) doped with varying weight percent of nitrogen (N) as a photocatalyst. ZnO/GS was synthesized via co-precipitation with zinc nitrate hexahydrate and papaya leaf extract in an aqueous solution, which will be further doped using urea as nitrogen doping. Characterization techniques, including FESEM, EDX, FTIR, and XRD, were employed to analyze the morphology, structural characteristics, surface, and pore volumes of nitrogen-doped green synthesized zinc oxide (N-ZnO/GS). The photocatalytic performance of these samples was evaluated through the photodegradation of methylene blue dye under visible light irradiation. The sample with 10wt%, which is 1 g of dopant, exhibited the optimal results, indicating a homogeneous surface and high crystallinity of N-ZnO/GS synthesized via co-precipitation, demonstrating the best photodegradation efficiency in the photocatalysis process. The findings suggest potential applications in environmental remediation through the degradation of organic pollutants, enhancing wastewater treatment efficacy.